Chiral Materials: Chiral Surface Lattice Resonances (Adv. Mater. 22/2020). Issue 22 (2nd June 2020) - Goerlitzer, Eric S. A.; Mohammadi, Reza; Nechayev, Sergey; Volk, Kirsten; Rey, Marcel; Banzer, Peter; Karg, Matthias; Vogel, Nicolas
Abstract : Optical activity of surface lattice resonances is demonstrated by Nicolas Vogel and co‐workers in article number 2001330 . The controlled arrangement of chiral crescent‐shaped nanoantennae allows a selective response of the surface lattice resonances to the handedness of incident circularly polarized light. Modified colloidal lithtography enables the fabrication of cm 2 ‐scale substrates using a self‐assembled poly( N ‐isopropylacrylamide)–silica core–shell system as particle masks.